ANALISIS TINGKAT KEPUASAN TERHADAP KUALITAS LAYANANPENDIDIKAN DENGAN METODE SERVICE QUALITY DAN IMPORTANCE PERFORMANCE ANALYSIS DI SMK NEGERI 1 PALABUHANRATU - Rio Rokhmani (STISIP Widyapuri Mandiri Sukabumi, 2022)
Students are direct users of the education service system, so schools must provide satisfaction and positive trust to students so that they believe that they are in a place that is suitable for developing their potential to be ready to face competition in society. The purpose of this study was to determine the quality of education services at SMKN 1 Palabuhanratu and to find out what indicators need to be improved by SMKN 1 Palabuhanratu in order to improve service quality. This research method uses quantitative descriptive with Proportionate Stratified Random Sampling. The results showed that simultaneously the level of satisfaction of students at SMKN 1 Palabuhanratu with their education services was